Avoiding Deontic Explosion by Contextually Restricting Aggregation - Meheus, Joke; Beirlaen, Mathieu; Van De Putte, Frederik (Proceedings of the 10th International Conference on Deontic Logic in Computer Science (DEON 2010), 2010)
In this paper, we present an adaptive logic for deontic conflicts, called \sys{P2.1}$^r$, that is based on Goble's logic \sys{SDL}$a$\sys{P}$e$–-a bimodal extension of Goble's logic \sys{P} that invalidates aggregation for all prima facie obligations. The logic \sys{P2.1}$^r$ has several advantages with respect to \sys{SDL}$a$\sys{P}$e$. For consistent sets of obligations it yields the same results as Standard Deontic Logic and for inconsistent sets of obligations, it validates aggregation ``as much as possible''. It thus leads to a richer consequence set than \sys{SDL}$a$\sys{P}$e$. The logic \sys{P2.1}$^r$ avoids Goble's criticisms against other non-adjunctive systems of deontic logic. Moreover, it can handle all the `toy examples' from the literature as well as more complex ones.